SISTEM APLIKASI DATA PEGAWAI PENSIUN MENGGUNAKAN METODE K-MEANS - Seta Permana; Woro Isti Rahayu (Teknik Informatika, 2020)
Division or work unit of Human Resources (HR) in PT. Kawasan Berikat Nusantara (PT. KBN) (Persero) has job desks including finding and accepting new employees at PT. KBN, handles the process of receiving employee salaries, handles employee data management including employee retirement data. The problem with managing employee pension data is that there is no system that can handle this. So this research aims to be able to help in making a system that fits the needs for managing retirement employee data. By determining the pension application for employees at the age of 51-53 years with an existing position at PT. KBN, namely, head of division, section head, section head, and executive. In determining this, the Clustering method will be used, namely K-means. This method is considered appropriate because it can group data based on the Cluster 's closest center point with the data. Classification of employees based on age and position into 2 groups, namely the submission of pensions at the age of 51 years filing a pension submission of retirement at the age of 53. From the results that have been calculated from 56 data of employees aged 51-53 years resulted in 21 employees being submitted in retirement age 51 years, 35 employees in filing retirement 53 years.